Valuation : measuring and managing the value of companies (New York : John Wiley & Sons, 2000)
This book is divided into three parts: Company value and the Manager's mission; Cash flow valuation: A practitioner's guide; and Applying valuation.
Keywords: Corporations; Valuation; Corporations -- Valuation -- Handbooks, manuals, etc